Clinical pharmacist and health management: an integrating literature review (Research, Society and Development, 2019)
The objective of this study was to identify and analyze the Brazilian scientific production on health management and clinical pharmacy, from 2011 to 2018. The aim was to present the Health Management and Clinical Pharmacy, based on the publications of scientific articles, seeking the role of the clinical pharmacist helping patients, as users of Health Unic System of Brazil, in the rational use of medicines and in improving the quality of pharmacotherapy. The search for the articles was done through the “Biblioteca Virtual em Saúde (BVS)” using the terms "Clinical Pharmacy" and "Health Management" from 2011 to 2018. Most of the articles were published in 2012 and the journal with the highest number of publications was “Ciência & Saúde Coletiva”. The selected articles were grouped into four categories according to their themes: Pharmaceutical Care, Pharmaceutical Care, Clinical Pharmacy and Pharmaceutical Assistance Management. Although Pharmaceutical Assistance in the Health Unic System of Brazil has existed for 30 years and public policies guarantee its execution, there are still problems in the access and rational use of medicines. Without medicines, adequate structure and efficient management it is not possible to perform clinical, legally protected pharmaceutical services.